2021
DOI: 10.5194/nhess-2021-250
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insights from the topographic characteristics of a large global catalog of rainfall-induced landslide event inventories

Abstract: Abstract. Landslides are a key hazard in high-relief areas around the world and pose a risk to population and infrastructure. It is important to understand where landslides are likely to occur in the landscape to inform local analyses of exposure and potential impacts. Large triggering events such as earthquakes or major rain storms often cause hundreds or thousands of landslides, and mapping the landslide populations generated by these events can provide extensive datasets of landslide locations. Previous wor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
(92 reference statements)
2
1
0
Order By: Relevance
“…CTI intrinsically contains information on the potential hydrological conditions of the site (through the catchment area) as well as its slope. In line with our study, Emberson et al (2021) found that the CTI is a strong predictor of rainfall-induced landslides for a number of inventories in the tropics and subtropics. Earlier global LSS maps by Nadim et al (2006), Hong et al (2007) 290 and Stanley and Kirschbaum (2017) primarily used slope information, while Lin et al (2017) use relative relief.…”
Section: Selected Predictor Variablessupporting
confidence: 91%
“…CTI intrinsically contains information on the potential hydrological conditions of the site (through the catchment area) as well as its slope. In line with our study, Emberson et al (2021) found that the CTI is a strong predictor of rainfall-induced landslides for a number of inventories in the tropics and subtropics. Earlier global LSS maps by Nadim et al (2006), Hong et al (2007) 290 and Stanley and Kirschbaum (2017) primarily used slope information, while Lin et al (2017) use relative relief.…”
Section: Selected Predictor Variablessupporting
confidence: 91%
“…Instead, with ϕ = θ in the range 30°-50°, we obtain cohesions between 2 and 10 kPa, values that are typical for shallow landslides (Gabet et al, 2004;von Ruette et al, 2014;Wu & Sidle, 1995). This is consistent with recent studies where landslide susceptibility (whether triggered by rainfall or earthquakes) was found to scale with slope normalized by the landscape median rather than absolute slope, suggesting that mechanical strength (i.e., ϕ) is adjusted to the landscape (i.e., θ) (Emberson et al, 2021;Marc et al, 2018;Milledge et al, 2019). Furthermore, fixing C = 4,000 kPa in Equation 4and solving for ϕ yields a strong correlation between ϕ and θ and a reduced ϕ value in 2015 (Figures S4 and S5 in Supporting Information S1).…”
Section: Sensitivity To Under-constrained Model Parameterssupporting
confidence: 90%
“…The effects of climate change are likely to increase the frequency of occurrence of landslides (Gariano & Guzzetti, 2016). Rivers in the Philippines are particularly dynamic, with fluctuating sediment supply from landslides (Abancó et al, 2021;Catane et al, 2012;Emberson et al, 2022), earthquakes (Atkinson, 1995), volcanoes (Gran et al, 2011) and anthropogenic activities such as dam construction for water supply, hydropower and mine tailings (Tabios III, 2020) contributing to globally high river migration rates (Dingle et al, 2019). Emblematic of this dynamism, high rates of river planform adjustment have been observed in the vicinity of bridge infrastructure (Boothroyd et al, 2021).…”
Section: The Philippinesmentioning
confidence: 99%